The contribution of posters to the venereal disease campaign in Second World War Britain. Issue 4 (2nd October 2022) - Lewis, Bex; Warnaby, Gary
ABSTRACT: In 1942, the British government placed large posters addressing the 'problem' of venereal disease (VD) in prominent public spaces, as an attempt to manage this 'threat' exacerbated by war. Utilising extensive archival research, this article uses the VD campaign as a lens to examine the way that the state sought to change attitudes and behaviour, and the role of posters in such attempts. With posters reflecting the most publicly acceptable discourses relating to VD, the article investigates state action and public responses, through themes of 'The People's War', medical and moral messages, and discourses of shadows and the home.